EFFECTS OF DIFFERENT DOSES OF MEDETOMIDINE ON CLINICAL AND HEMATOLOGICAL PARAMETERS IN DOGS - H. Akbar; M. A. Khan; M. A. Khan; M. S. Khan; S. Aslam; A. Nasir; A. A. Anjum (Journal of Animal and Plant Sciences, 2014)
Medetomidine HCl was clinically evaluated as anesthetic at various doses on the basis of sedative, analgesic and hematologic effects in mongrel dogs under experimental conditions. Clinically healthy dogs (n=50) divided randomly in groups A, B, C, D and E (n=10, each) were injected with normal saline and 15, 30, 45 and 60 µgm/Kg body weight medetmidine HCl, respectively. It was noticed that body temperature, pulse and respiratory rates tends to decrease overall at various doses in treated dogs compared to control. Blood pressure of the dogs in experimental groups showed slight decline in values than control. Extent of sedation and analgesia was more prominent at higher doses. Maximum decrease of Serum alkaline phosphatase (SAP) concentration was observed in group B (131.4±10.2; 133.2±22.5) at 20 and 40 minutes post drug administration and at 60 minutes (125.4±10.0) in group E. The highest fall in Aspartate transaminase (AST) values was seen in group E (31.6±2.4, 34.2±2.8 and 35.9±2.0) at 20, 40 and 60 minutes. Alanine transaminase (ALT) values significantly declined in dogs of group B (42.5±9.1, 34.7±6.5 and 35.9±8.0) in relation to selected timings. Urea levels differed non-significantly with control and decrease in creatinine level was significant in groups E (0.67±7.8). D (0.85±.29) and B (0.97±.22) compared to control. At 20, 40 and 60 minutes post drug administration value of uric acid increased significantly in group D (0.74±0.11), B (0.67±17) and C (0.73±.11) than control.  At different time intervals post anesthetic administration hemoglobin levels in group D was 11.95±1.47, 12.08±1.12 and 12.9±2.47 which showed significant difference with control (14.01±1.37). Non-significant differences were observed in values of total leucocytes count (TLC), differential leucocytes count (DLC) and erythrocyte sedimentation rate (ESR) in dogs of treated and control groups with different doses in relation to time. Results depicted that in group B (15µgm/Kg body weight) parameters recorded were efficient to declare the dose of drug safe for maintenance of anesthesia with no side effects.
Keywords: Anesthesia; Sedation; Analgesia; Recovery; Hematology and Medetomidine HCl